Evaluating the role of Ubiquitin D gene expression in types of leukemia: UBD gene expression in leukemia - Zhao, Lei; Liu, Dongxu; Zhong, Cailing; Tang, Siqi; Li, Xiaojun; Zhu, Mengyu; Li, Chunying (Cellular and Molecular Biology, 2022)
Using animal models to develop new treatments is essential, especially in diseases like cancer. In this study, we induced leukemia by intravenous injection of cancer cells (BCL1 cell line) and the examination of cell markers in the animal’s blood to study the changes in the expression of the UBD gene as a biomarker for diagnosing and examining the progress of the disease. For this purpose, five million BCL-1 cells were injected into the tail vein of BALBIe mice of the same breed. Fifty mice were killed after four weeks, and we examined peripheral blood cells and histological changes. Then RNA of the samples was extracted, and cDNA synthesis was done with the help of MMuLV enzyme, Oligo dT, and Random hexamer primers. Specific primers for UBD were designed using Primer Express software, and the expression level of the UBD gene was measured by the method. The results showed that in the CML group, the lowest expression level was 1.70 times, and in the ALL group, the highest expression level was 7.97 times compared to the control group. The average increase in UBD gene expression was 3.21 times in the CLL group and 4.94 times in the AML group. The UBD gene can be further investigated so that it may be used as a proposed biomarker for the diagnosis of leukemia. Therefore, the evaluation of the expression level of this gene can be used to diagnose leukemia. However, more studies than the currently applied methods are needed in cancer diagnosis, which has many errors compared to the technique used in this study, and to prove its accuracy and sensitivity.